Alat Pendeteksi Asap Rokok Pada Ruangan Tertutup - ANDI, HERI (ENERGI & KELISTRIKAN, 2023)
Air has a very important meaning in the life of living things. To get air according to the desired quality level, air pollution control is very important to do. Indoor air quality is a problem that needs attention because it will affect human health. According to the National Institute of Occupational Safety and Health (NIOSH) 1997, the causes of indoor air quality problems are generally caused by several things, namely lack of air ventilation (52%), sources of contaminants indoors (16%), contaminants from outside room (10%), microbes 5%, building materials (4%), others (13%). The purpose of this research is to make a tool that can detect cigarette smoke in a closed room. This system is based on the Internet of Things (IoT) which is equipped with an MQ-2 sensor and a website that is used for monitoring the tool. The research method was carried out using the waterfall method with data taken based on sensor results from this tool. The test results used the black box test method which produced a percentage of 87.7%. so that it can be concluded that the cigarette smoke detector in this closed room is running well and as needed.